2014
DOI: 10.4236/oalib.1100747
|View full text |Cite
|
Sign up to set email alerts
|

Scalp Reconstruction Using Integra, an Alternative to Free Tissue Transfer—Case Report

Abstract: We present a case of scalp reconstruction using Integra  and split skin grafting after extensive excision of melanoma in a previously irradiated field. Radical resection of malignancy and application of Integra  , a dermal substitute, was performed. Following histological confirmation of complete excision, a split-thickness skin graft (SSG) was applied. After 14 months the patient remains fully healed and without recurrence. The 2-stage use of Integra  and SSG is useful in reconstructing large scalp defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Five studies reported time to second stage >30 days. 12,14,20,24,36,37 All five reported a complication accounting for the delay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported time to second stage >30 days. 12,14,20,24,36,37 All five reported a complication accounting for the delay.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 22 articles using unfenestrated Integra reported percent take ranging from 50% to 100%. 911,1416,1820,2225,27,3135,37,39,42 Fung et al 37 reported hematoma formation under unfenestrated Integra resulting in 90% graft take.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2stage use of Integra, followed by SSG was successful, and after 14 months the patient was fully healed with no recurrence. 22 Similarly, Cunningham et al obtained successful results with Integra followed by negative pressure wound therapy (NPWT) in a 63year-old man with numerous superficial and invasive SCC of the scalp that required excision of a total area of 400 cm 2 . 23…”
Section: Complex Wounds and Bone Exposurementioning
confidence: 98%
“…In terms of dressing the most commonly used options were bolstered dressing, 15,17,19,22,24,26,32,33 silver-impregnated dressing 6,16,25 and NPWT, 12,23,28,34,35 which is effective in reducing shearing forces across the surface of the dermal matrix by acting as a splint and forces the material on to the wound bed. The authors recommendation is to perform the dressing with nonadherent wound contact layer (eg, fatty gauze) on top and apply Betadine gel (Braunol; B. Braun, Milan, Italy), silver sulfadiazine or other silver dressings to the edge, followed by traditional compressive over the bandage.…”
Section: Tumor Characteristicsmentioning
confidence: 99%